2003
DOI: 10.1046/j.1523-1755.2003.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 expression and leukocyte accumulation in inner stripe of outer medulla in early phase of ischemic compared to HgCl2-induced ARF

Abstract: After HgCl2, almost no leukocyte accumulation and up-regulation of ICAM-1 was observed the first 12 hours after injury. In contrast, very early after I/R injury, increased expression of ICAM-1 goes along with monocyte and T-cell accumulation in the ISOM, endorsing this particular zone as critical in renal I/R injury. These observations contribute to the understanding why anti-ICAM-1 treatment in acute I/R injury is successful, but fails in acute toxic injury induced by HgCl2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…Secondary inflammation plays a major role during ischemic AKI, 2 and ICAM-1 expression is known to increase and to contribute to progressive tissue damage. 24,37 Changes of ICAM-1 were detected in many of the cases despite the short time frame of the study. Cell necrosis and apoptosis were not expected because they develop only after a delay.…”
Section: Discussionmentioning
confidence: 92%
“…Secondary inflammation plays a major role during ischemic AKI, 2 and ICAM-1 expression is known to increase and to contribute to progressive tissue damage. 24,37 Changes of ICAM-1 were detected in many of the cases despite the short time frame of the study. Cell necrosis and apoptosis were not expected because they develop only after a delay.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it could be concluded that the level of these chemoattractants was not responsible for the diminished PMN/MO infiltration in uPAR Ϫ/Ϫ allografts. Adhesion molecules are rapidly up-regulated early after transplantation (55) and after induction of IR injury (56). Therefore, we analyzed expression of ICAM-1 in WT2 and uPAR Ϫ/Ϫ allografts given the facts that, being the major counterreceptor for leukocyte ␤2-integrins, this adhesion molecule is rapidly up-regulated within the first 2-3 h after transplantation (57) and the blockade of ICAM-1 strongly attenuated PMN infiltration in some experimental models of renal ischemia (58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…TLR expression was highest in outer medullary cells, the area with the greatest amount of inflammation after ischemic AKI (97). The time course of TLR4 expression following injury was highest at 4 hours, the same point at which the microvasculature begins to show dysfunction (75).…”
Section: Endotheliummentioning
confidence: 98%